Oriented Two-Dimensional Covalent Organic Framework Films for Near-Infrared Electrochromic Application - Hao, Qing; Li, Zhi-Juan; Lu, Cheng; Sun, Bing; Zhong, Yu-Wu; Wan, Li-Jun; Wang, Dong (Journal of the American Chemical Society, 2019)
The electrochromic property and device construction of a triphenylamine-based oriented two-dimensional covalent organic framework (2D COF) film on indium tin oxide (ITO) coated glass was reported. The characterization of the 2D COF3PA‑TT film revealed that the film was uniform, with good crystallinity, and oriented with its 2D plane parallel to the substrate. For the first time, the electrochromic properties of 2D COF3PA‑TT film were studied. 2D COF3PA‑TT film on ITO exhibited reversible color transition between deep red and dark brown during redox process. Spectroelectrochemical experiments revealed color changes in the absorption spectra of 2D COF3PA‑TT film in the visible and near-infrared regions and showed the characteristics of intervalence charge transfer. The quasi-solid-state electrochromic device was prepared based on the COF3PA‑TT film, and it exhibited moderate performance and stability in the near-infrared region.